PELATIHAN PEMASARAN UNTUK MENINGKATKAN PENJUALAN MINUMAN MANGGA DENGAN PEMASARAN BERBASIS E-COMMERCE DI DESA KARANG ENDAH - Al Muhariah, Novie; Irawan, Andri; Primandari, Novegya Ratih; Akbar, Ali; Dahlia, Dahlia; Kusuma, Maulana Hadi; Sandy, Ajeng Herlita (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2024)
Economic problems are inseparable from the social life of society. Innovative and developmental ideas are needed to improve the economy, especially in building micro and macro businesses. In Karang Endah Village, mangoes are not further processed before being marketed so that their selling value cannot increase. In addition, Karang Endah villagers also lack understanding of the use of social media as an e-commerce platform to market their products. Therefore, residents in Karang Endah Village and Baturaja University made a business idea, namely the development of mango fruit products into contemporary products (Manggo Sago) with e-commerce-based marketing in Karang Endah Village, Lengkiti District to develop village potential for economic activities and the results turned out that mango fruit can be a product that can be used as an attractive business with a higher selling price compared to mango fruit before processing, this business is also easier with e-commerce-based marketing using several media such as Instagram, Facebook, Shopee, Youtube and others.